Collaborative Social Accountability in Fragile Settings : Lessons from Guinea, Niger, and Tajikistan - Poli, Maria; Meknassi, Saad; Thindwa, Jeff; Kumagai, Saki; Cavatore, Maria; Jespersen, Ann-Sofie (World Bank, Washington, DC, 2020)
The United Nations and World Bank jointly urge a shift away from managing crises toward prevention through inclusive and collective interventions (United Nations and World Bank 2018). Collaborative social accountability—a process where citizens and civil society actors engage with state actors in joint, iterative problem solving to improve service delivery, sector governance, and accountability—can make an important contribution to this goal. Citizen engagement, and within that social accountability, can potentially help to strengthen the social contract and build state legitimacy. A consensus is emerging among scholars that state legitimacy is enhanced not by service delivery alone but by the opportunities the process provides for citizens to interact positively with the state. Inclusive citizen engagement involving women, youth, and other traditionally excluded groups in decision-making is fundamental to sustaining peace. Formal and informal civil society organizations (CSOs) can play critical roles by representing citizen interests and preferences, enabling citizens to hold government to account, facilitating collaboration of citizens and state actors, and involving coalitions of stakeholders. Supported by the State and Peacebuilding Fund (SPF), the Global Partnership for Social Accountability (GPSA) piloted collaborative social accountability approaches that bring together citizens, CSOs, and the state actors in Guinea, Niger, and Tajikistan from September 2018 to December 2019. This note aims to capture the activities and lessons learned as a resource for World Bank operations teams.